Linoleic Acid Alleviates Lipopolysaccharide Induced Acute Liver Injury via Activation of Nrf2 - Zhang, Q; Jiang, Y; Qin, Y; Liu, J; Xie, Y; Zhang, L; Li, K; Wang, X; Liu, G (Physiological research, 2024)
Linoleic acid (LA) not only functions as an essential nutrient, but also profoundly modulates oxidative stress and inflammatory response. However, the potential mechanisms have not been adequately researched. Hence, this study examined the potential pharmacological roles of LA and the underlying mechanisms in mice with lipopolysaccharide (LPS)-associated acute liver injury (ALI). The results indicated that treatment with LA alleviated the histopathological abnormalities in the hepatic and plasma levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and glutathione-S-transferase (GST) in mice with LPS exposure. In addition, LA inhibited the LPS-associated generation of proinflammatory factors, such as tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6), and downregulated the hepatic myeloperoxidase (MPO) level. In addition, the administration of LA resulted in a reduction in hepatic malondialdehyde (MDA) levels and an elevation in liver superoxide dismutase (SOD), reduced glutathione (GSH), catalase (CAT), and glutathione peroxidase (GSH-PX) levels. Further investigations revealed that LA promoted the expression of nuclear factor E2-related factor (Nrf2) and NAD(P)H: quinone oxidoreductase 1 (NQO1). In addition, the beneficial outcomes of LA on LPS-induced acute liver failure were revered when Nrf2 was pharmacologically suppressed by ML385. These experimental results demonstrated that LA supplementation attenuated LPS-associated acute hepatic impairment in mice via the activation of Nrf2.
Keywords: Liver; Animals; lipopolysacharidy; kyselina linolová; oxidační stres; Chemical and Drug Induced Liver Injury; Oxidative Stress; Lipopolysaccharides; Mice; játra; NF-E2-Related Factor 2; Linoleic Acid; Male; mužské pohlaví; faktor 2 související s NF-E2; myši; zvířata; lékové postižení jater